TANTANGAN TRANSFORMASI DIGITAL DALAM PENDIDIKAN ISLAM DI ERA SOCIETY 5.0: STUDI PADA IAIN CURUP - Dwi Oktasari; Jenny Fransiska; Yusman Haris; Lukman Asha; Ifnaldi Ifnaldi; Dina Hajja Ristianti (Jurnal Manajemen Pendidikan, 2026)
Digital transformation in Islamic education is an inescapable necessity in the Society 5.0 era; however, the process faces complex and multi-layered challenges, particularly for State Islamic Religious Higher Education Institutions (PTKIN) that must integrate Islamic values with digital technology demands. Previous research has generally examined digital transformation in Islamic education at a macro level without considering specific institutional contexts, leaving a knowledge gap regarding the concrete challenges faced by PTKIN in implementation. This study aims to identify and analyze the challenges of digital transformation in Islamic education in the Society 5.0 era and the strategies for addressing them at IAIN Curup. A qualitative phenomenological approach was used, involving 30 participants including institutional leaders, lecturers, educational staff, and students selected through purposive and snowball sampling. Data were collected through in-depth phenomenological interviews, systematic observation, and documentation study, then analyzed using Interpretative Phenomenological Analysis (IPA). The results reveal six main challenge clusters: (1) intergenerational digital competency gaps; (2) tension between traditional Islamic education values and the digital paradigm; (3) uneven technology infrastructure; (4) organizational culture resistance; (5) limited budgets for digital development; and (6) a lack of contextual digital-based Islamic education pedagogical models.